EFFECTIVENESS OF ONLINE TEACHING BY USING WHATSAPP MESSENGER TO TEACH WRITING ON REPORT TEXT AT THE ELEVENTH GRADE OF MA SEJAHTERA PARE - KEDIRI - M. Syaichul Muchyidin; Muslih Fajri (Politeknik Negeri Bengkalis, 2021)
Teaching writing is not as easy as teaching reading or speaking. On some cases, it sometimes shows monotonous method so that most students feel bored; moreover, they do not understand the material at all. In teaching writing, the teacher must be creative to make students understand the material because writing is a difficult arithmetic number. It aims to determine if the method is effective to teach writing or not in this pandemic era. This research used is pre-experimental design with one-shot case study. In this research, the researcher took one class as the sample. The subject research is eleventh grade. The instrument used in this thesis was test. In collecting the data, the writer used pre-test and post-test. Before conducting post-test, the writer gave treatment. After getting enough data, the researcher calculated the data by using SPSS to find out the effectiveness of online teaching by using WhatsApp messenger in teaching writing of report text. Based on the result of the pre-test and post-test , it shows that there is a difference significance between pre-test and post-test and teaching writing by using WhatsApp messenger is one of the effective way. It is also supported by Dumanauw (2018) on the research. It shows that The use of WhatsApp to teach writing of recount text is succeeded in increasing students’ writing achievement.